Regulatory role of the endocannabinoid system on glial cells toward cognitive function in Alzheimer’s disease: A systematic review and meta-analysis of animal studies - Kamaruzzaman, Mohd Amir; Romli, Muhammad Hibatullah; Abas, Razif; Vidyadaran, Sharmili; Hidayat Baharuldin, Mohamad Taufik; Nasaruddin, Muhammad Luqman; Thirupathirao, Vishnumukkala; Sura, Sreenivasulu; Warsito, Kabul; Mohd Nor, Nurul Huda; Azwaruddin, Muhammad Amsyar; Alshawsh, Mohammed Abdullah; et al. (Frontiers in Pharmacology, 2023)
Objective: Over the last decade, researchers have sought to develop novel medications against dementia. One potential agent under investigation is cannabinoids. This review systematically appraised and meta-analyzed published pre-clinical research on the mechanism of endocannabinoid system modulation in glial cells and their effects on cognitive function in animal models of Alzheimer’s disease (AD). Methods: A systematic review complying with PRISMA guidelines was conducted. Six databases were searched: EBSCOHost, Scopus, PubMed, CINAHL, Cochrane, and Web of Science, using the keywords AD, cannabinoid, glial cells, and cognition. The methodological quality of each selected pre-clinical study was evaluated using the SYRCLE risk of bias tool. A random-effects model was applied to analyze the data and calculate the effect size, while I2 and p-values were used to assess heterogeneity. Results: The analysis included 26 original articles describing (1050 rodents) with AD-like symptoms. Rodents treated with cannabinoid agonists showed significant reductions in escape latency (standard mean difference [SMD] = −1.26; 95% confidence interval [CI]: −1.77 to −0.76, p < 0.00001) and ability to discriminate novel objects (SMD = 1.40; 95% CI: 1.04 to 1.76, p < 0.00001) compared to the control group. Furthermore, a significant decrease in Aβ plaques (SMD = −0.91; 95% CI: −1.55 to −0.27, p = 0.006) was observed in the endocannabinoid-treated group compared to the control group. Trends were observed toward neuroprotection, as represented by decreased levels of glial cell markers including glial fibrillary acid protein (SMD = −1.47; 95% CI: −2.56 to −0.38, p = 0.008) and Iba1 (SMD = −1.67; 95% CI: −2.56 to −0.79, p = 0.0002). Studies on the wild-type mice demonstrated significantly decreased levels of pro-inflammatory markers TNF-α, IL-1, and IL-6 (SMD = −2.28; 95% CI: −3.15 to −1.41, p = 0.00001). Despite the non-significant decrease in pro-inflammatory marker levels in transgenic mice (SMD = −0.47; 95% CI: −1.03 to 0.08, p = 0.09), the result favored the endocannabinoid-treated group over the control group. Conclusion: The revised data suggested that endocannabinoid stimulation promotes cognitive function via modulation of glial cells by decreasing pro-inflammatory markers in AD-like rodent models. Thus, cannabinoid agents may be required to modulate the downstream chain of effect to enhance cognitive stability against concurrent neuroinflammation in AD. Population-based studies and well-designed clinical trials are required to characterize the acceptability and real-world effectiveness of cannabinoid agents. Systematic Review Registration: [https://inplasy.com/inplasy-2022-8-0094/], identifier [Inplasy Protocol 3770].